2016
DOI: 10.1111/pce.12858
|View full text |Cite
|
Sign up to set email alerts
|

The use of NH4+ rather than NO3 affects cell stoichiometry, C allocation, photosynthesis and growth in the cyanobacterium Synechococcus sp. UTEX LB 2380, only when energy is limiting

Abstract: The assimilation of N-NO requires more energy than that of N-NH . This becomes relevant when energy is limiting and may impinge differently on cell energy budget depending on depth, time of the day and season. We hypothesize that N-limited and energy-limited cells of the oceanic cyanobacterium Synechococcus sp. differ in their response to the N source with respect to growth, elemental stoichiometry and carbon allocation. Under N limitation, cells retained almost absolute homeostasis of elemental and organic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 73 publications
3
21
0
Order By: Relevance
“…Interestingly, the NR activity in NO − 3 -grown cells under low CO 2 was higher in P i -replete than in P i -limited cells, supporting the assumption that an increased energy demand, in terms of ATP, for NO − 3acquisition (Ruan & Giordano, 2017) was also present in C. acidophila.…”
Section: Adaptations To Acidic Environment-nr Activitysupporting
confidence: 58%
See 2 more Smart Citations
“…Interestingly, the NR activity in NO − 3 -grown cells under low CO 2 was higher in P i -replete than in P i -limited cells, supporting the assumption that an increased energy demand, in terms of ATP, for NO − 3acquisition (Ruan & Giordano, 2017) was also present in C. acidophila.…”
Section: Adaptations To Acidic Environment-nr Activitysupporting
confidence: 58%
“…It was previously shown that the influence of the N i ‐source on different physiological parameters might depend on other factors, such as light (Ruan & Giordano, ) and CO 2 (Giordano, ), but to our knowledge there are no studies combining two factors involved in energy and carbon metabolism in comparison with the effect of a different N i ‐source. Therefore, as both C i (Tittel, Bissinger, Gaedke, & Kamjunke, ) and P i (Spijkerman ) have been identified as potential (co‐)limiting factors for C. acidophila in the acidic Lake 111 (Spijkerman, Stojkovic, Holland, Lachmann, & Beardall, ), we included both factors in our setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of a nutrients remineralization via grazer metabolism was proposed by the authors, but the likelihood of such hypothesis depends on the nutritional and energetic context in which the interspecific interaction occurs. A stimulation of growth by nutrient regeneration can only occur in algae whose growth is limited by the same regenerated nutrient and/or by the energy availability (when regeneration makes a nutrient available in a form that requires less energy for assimilation than the form it was originally assimilated; e.g., NH 4 + vs. NO 3 − ; Ruan and Giordano , Ruan et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Also a N and energy co‐limitation can be envisaged: H‐CO 2 cells and LL cells were grown in NO 3 − in semicontinuous cultures and then transferred, at the beginning of the grazing experiments, to a medium (control conditions) containing the same concentration of NO 3 − than the media of origin. The release of an alternative source of N through regeneration by zooplankton, under energy limitation, may have stimulated growth because of the lower cost of NH 4 + than NO 3 − assimilation (e.g., Ruan and Giordano , Ruan et al. ), and the consequent greater availability of energy for growth.…”
Section: Discussionmentioning
confidence: 99%